Non-financial disclosure and firm performance: Insights from listed consumer goods manufacturing companies in Nigeria - Muyiwa Emmanuel Dagunduro; Gbenga Ayodele Falana; Joseph Omotoso Ajayi; Olayinka Dominion Boluwaji (Economy, Business and Development: An International Journal (EB&D), 2024)
In the dynamic landscape of corporate reporting and stakeholder engagement, the significance of non-financial disclosure has gained considerable prominence. As businesses strive for sustainable growth and investors increasingly recognize the value of environmental, social, and governance (ESG) factors, understanding the nexus between non-financial disclosure and firm performance becomes pivotal. This study endeavors to explore this relationship within the context of listed consumer goods manufacturing firms in Nigeria. The study encompassed a population of 21 listed consumer goods manufacturing firms in Nigeria. The sample size was 21 firms, determined through census sampling techniques. The research spanned from 2013 to 2022. FGLS regression model was used to examine the relationship between the variables studied. The results found that environmental disclosure and social disclosure had a positive and significant effect on the firm's performance. While governance disclosure had a negative and significant effect on the firm's performance. This implies that firms that engage in robust non-financial disclosure practices tend to experience better overall performance. The study concludes that non-financial disclosure, encompassing environmental, social, and governance aspects, plays a pivotal role in influencing the performance of listed consumer goods manufacturing firms in Nigeria. Firms are encouraged to enhance their ESG reporting frameworks, aligning with stakeholder expectations and global sustainability trends.
Keywords: M14; 330; environmental disclosures; firm performance.; governance disclosures; non-financial disclosure; social disclosures